Cycles of myofiber degeneration and regeneration lead to remodeling of the neuromuscular junction in two mammalian models of Duchenne muscular dystrophy. - Seth G Haddix; Young Il Lee; Joe N Kornegay; Wesley J Thompson (PLoS ONE, 2018)
Mice lacking the sarcolemmal protein dystrophin, designated mdx, have been widely used as a model of Duchenne muscular dystrophy. Dystrophic mdx mice as they mature develop notable morphological abnormalities to their neuromuscular junctions, the peripheral cholinergic synapses responsible for activating muscle fibers. Most obviously the acetylcholine receptor aggregates are fragmented into small non-continuous, islands. This contrasts with wild type mice whose acetylcholine receptor aggregates are continuous and pretzel-shaped in appearance. We show here that these abnormalities in mdx mice are also present in a canine model of Duchenne muscular dystrophy and provide additional evidence to support the hypothesis that NMJ remodeling occurs due to myofiber degeneration and regeneration. Using a method to investigate synaptic AChR replacement, we show that neuromuscular junction remodeling in mdx animals is caused by muscle fiber degeneration and regeneration at the synaptic site and is mimicked by deliberate myofiber injury in wild type mice. Importantly, the innervating motor axon plays a crucial role in directing the remodeling of the neuromuscular junction in dystrophy, as has been recorded in aging and deliberate muscle fiber injury in wild type mice. The remodeling occurs repetitively through the life of the animal and the changes in junctions become greater with age.